Identification of a specific region of low molecular weight phospholipases A2 (residues 21-40) as a potential target for structure-based design of inhibitors of these enzymes. - Cordella-Miele, E (1993)
We have identified a specific region of porcine pancreatic phospholipase A2 (residues 21-40) which interacts with a neutralizing antibody causing a dramatic inhibition of its enzymatic activity (Ki in the order of 10(-8) M). The binding equilibrium of the antibody-phospholipase A2 complex is reached in < 3 min at 37 degrees C. Fab fragments are equally effective phospholipase A2 inhibitors, as are intact IgG molecules. The inhibition is virtually complete and noncompetitive with respect to phosphatidylcholine substrate. The formation of precipitating immunocomplexes is not involved in the inhibition. The region of phospholipase A2 (residues 21-40) recognized by this antibody includes a highly conserved sequence which contains several functionally important residues of both group I and group II phospholipases A2. These data suggest that amino acid residues in this region of porcine pancreatic phospholipase A2 are accessible for interaction with inhibitors such as neutralizing antibodies and that agents specifically interacting with this region may have potent phospholipase A2 inhibitory activity. Thus, this conserved region of low molecular weight, extracellular phospholipases A2 is a potential target for structure-based design of specific noncompetitive inhibitors of these enzymes. Since these extracellular phospholipases A2 are suggested to play a pathogenic role in several important human diseases, the development of such pharmacologic inhibitors is of potential clinical importance.